Identity of Handling Water Pollution Caused by Petroleum Pollution in Indonesia by Adsorption: A Review - Monika Putri Pardede; Superlesman Laia; Hilfi Pardi (Publikasi Indonesia, 2024)
Indonesia is a maritime country known for its vast territorial waters of sea, reservoirs, rivers, lakes, and bays compared to its land area which makes Indonesia rich in natural resources of sea and other waters. However, many problems are faced when preserving the sea such as marine pollution in the form of petroleum spills which are very dangerous for marine ecosystems. Therefore, there needs to be a handling effort to overcome this. The purpose of this research is to provide information about handling by adsorption to overcome petroleum pollution. The preparation method is carried out by analyzing articles from various literature sources such as journals, scientific papers, report books, and Google Scholar. The conclusion is that the treatment that can be applied to overcome the pollution of the sea and other waters due to petroleum in Indonesia by adsorption using activated carbon cassava peel, cocoa pod skin, water hyacinth, banana peel, and banana stem is classified as effective, efficient and economical management and has its advantages in reducing the levels of parameters contained in petroleum waste.